Kajian sifat konduktansi membran kitosan pada berbagai variasi waktu perendaman dalam larutan Pb (Study of the conductance properties of chitosan membranes at various immersion times in Pb solution) - Mella Roza; - Gusnedi; - Ratnawulan (PILLAR OF PHYSICS, 2013)
Chitosan membrane is capable of being used as adsorbent adsorption of metal ions Pb. Assessment of the electrical properties of the chitosan membrane is one see references in the membrane as ability adorpsi metal ion weight. The purpose of this study to determine the nature of the conductance of chitosan membranes useful to look at the ability of the membrane chitosan as the adsorption of metal ions Pb. This research is experimental research with samples of chitosan membranes were soaked in a solution of Pb metal. The time variation of soaking the membrane is 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours and without soaking. The measurement results for the effect of soaking variation time chitosan membrane. Pb metal in solution obtained current-voltage characteristics of the membrane in the solution is linear, the longer soaking in a solution of Pb metal, the greater the current flow. The longer the time soaking in a solution of Pb chitosan membrane, then the greater the value of the conductance. Keywords : Chitosan, Membrane, Adsorption, Conductance, Metal Pb